Respuesta :
Answer:
Step 3
Step-by-step explanation:
Step 3 should be:
−6m + 6m = −48 − 12n + 4n + 4
9514 1404 393
Answer:
Step 3
Step-by-step explanation:
When the equations are added in step 3, the result should be ...
-6m +6m = -48 -12n +4 +4n
In the work shown, the (+4) was left out in Step 3.
__
When the work is properly continued, it becomes ...
Step 4: 0 = -44 -8n . . . . [step 3 is simplified]
Step 5: n = -5.5 . . . . . . . [step 4 is divided by -8 and 5.5 subtracted]
Step 6: m = -3 . . . . . . . . . [n is substituted into Equation 1]
And the solution is (m, n) = (-3, -5.5).